Periodic ethanol supply as a path toward unlimited lifespan of Caenorhabditis elegans dauer larvae - Zhang, Xingyu; Penkov, Sider; Kurzchalia, Teymuras V.; Zaburdaev, Vasily (Frontiers in Aging, 2023)
The dauer larva is a specialized stage of worm development optimized for survival under harsh conditions that has been used as a model for stress resistance, metabolic adaptations, and longevity. Recent findings suggest that the dauer larva of C. elegans may utilize external ethanol as an energy source to extend their lifespan. It was shown that while ethanol may serve as an effectively infinite source of energy, some toxic compounds accumulating as byproducts of its metabolism may lead to the damage of mitochondria and thus limit the lifespan of larvae. A minimal mathematical model was proposed to explain the connection between the lifespan of dauer larva and its ethanol metabolism. To explore theoretically if it is possible to extend even further the lifespan of dauer larvae, we incorporated two natural mechanisms describing the recovery of damaged mitochondria and elimination of toxic compounds, which were previously omitted in the model. Numerical simulations of the revised model suggest that while the ethanol concentration is constant, the lifespan still stays limited. However, if ethanol is supplied periodically, with a suitable frequency and amplitude, the dauer could survive as long as we observe the system. Analytical methods further help to explain how the feeding frequency and amplitude affect the lifespan extension. Based on comparison of the model with experimental data for fixed ethanol concentration, we propose the range of feeding protocols that could lead to even longer dauer survival and can be tested experimentally.